A Cadaveric Study of Anatomical Variations in the Course and Branching Pattern of the Median and Ulnar Nerves in the Palm - Sitwat Amna, Sabahat Zulfiqar, Afifa Waseem, Nimrah Fahim, Uzma Ali, Aneela Ahsan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anatomical variations in the course and branching pattern of the median and ulnar nerves in the palm hold significant clinical importance, particularly in the context of hand surgery, nerve repair, and regional anesthesia. Precise knowledge of these variations helps in minimizing iatrogenic injuries during surgical interventions. Objective: To examine and document the anatomical variations in the pathway and branching pattern of the median and ulnar nerves in the palm through a cadaveric study. Materials and Methods: This descriptive cadaveric study was conducted on 10 formalin-fixed adult human hands obtained from preserved cadavers in the anatomy department. Dissection was carefully performed in the palmar region to expose the median and ulnar nerves. Each hand was examined for the course of the nerves, number and pattern of branches, presence of communicating branches, and any unusual anatomical features. Results: Anatomical variations were identified in 4 out of 10 dissected hands (40%). The median nerve displayed variation in the origin and number of common palmar digital nerves in 2 hands. Ulnar nerve variations included aberrant branching and communicating branches with the median nerve in 2 specimens. No significant asymmetry between left and right hands was observed. Conclusion: The study demonstrated that anatomical variations in the median and ulnar nerves are relatively common even in a small sample size. These findings underscore the importance of preoperative anatomical awareness and careful dissection in surgical practice. Further large-scale studies are recommended to establish population-based anatomical baselines. Keywords: Median nerve, ulnar nerve, Hand anatomy, Cadaveric study, palmar nerves, Anatomical variation, Nerve branching